2022
DOI: 10.1016/j.redox.2021.102222
|View full text |Cite
|
Sign up to set email alerts
|

Role of glyoxalase 1 in methylglyoxal detoxification–the broad player of psychiatric disorders

Abstract: Methylglyoxal (MG) is a highly reactive α-ketoaldehyde formed endogenously as a byproduct of the glycolytic pathway. To remove MG, various detoxification systems work together in vivo , including the glyoxalase system, which enzymatically degrades MG using glyoxalase 1 (GLO1) and GLO2. Recently, numerous reports have shown that GLO1 expression and MG accumulation in the brain are involved in the pathogenesis of psychiatric disorders, such as anxiety disorder, depression, autism, and schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…As an enzyme protein-coding gene, GLO1 encodes glyoxalase I and is involved in detoxification of methylglyoxal (MG) in the cellular glycolysis pathway [ 35 ]. Previous studies have found that GLO1 expression and MG accumulation in the brain are associated with the pathogenesis of psychiatric disorders, such as anxiety disorder, depression, autism, and schizophrenia [ 36 ]. A recent hospital-based case-control study found significant differences in the distribution of GLO1 variation, RNA expression, and enzyme activity between schizophrenia patients and controls, suggesting GLO1 is associated with dysfunction in the left middle frontal gyrus in schizophrenia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an enzyme protein-coding gene, GLO1 encodes glyoxalase I and is involved in detoxification of methylglyoxal (MG) in the cellular glycolysis pathway [ 35 ]. Previous studies have found that GLO1 expression and MG accumulation in the brain are associated with the pathogenesis of psychiatric disorders, such as anxiety disorder, depression, autism, and schizophrenia [ 36 ]. A recent hospital-based case-control study found significant differences in the distribution of GLO1 variation, RNA expression, and enzyme activity between schizophrenia patients and controls, suggesting GLO1 is associated with dysfunction in the left middle frontal gyrus in schizophrenia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylglyoxal (MGO), a byproduct from the glycolytic pathway (and also from other metabolic pathways), is an intermediate of these non-enzymatic reaction sequences and is considered a main causative agent of glycation reactions in biological systems [36]. In fact, mammalian cells express a suitable enzymatic system for MGO detoxification, the glyoxalase system [37,38].…”
Section: Glycation Of ␣-Synucleinmentioning
confidence: 99%
“…N-Boc-L-Dap(N-Fmoc)-OH (18). Using a literature-reported procedure, 49 a slurry of Boc-L-asparagine (17, 5.0 g, 21.5 mmol) in ethyl acetate (24 mL), acetonitrile (24 mL), water (12 mL), and iodosobenzene diacetate (8.32 g, 25.8 mmol) was cooled and stirred at 16 °C for 30 min.…”
Section: Hclnh 2 -γ-L-glz[-l-cys(sh)-gly-ocpe]-ocpe (5)mentioning
confidence: 99%
“…It forms irreversible adducts with amino acids arginine and lysine, resulting in the formation of hydroimidazolone (MG-H1) and Nε-carboxyethyl-lysine (CEL), respectively . Under physiological conditions, MEG is detoxified by a conserved enzyme system, the ubiquitous glutathione (GSH)-dependent glyoxalase system (GLO), consisting of enzymes GLO1 and GLO2 . Reduced brain GLO1 function has been associated with the buildup of AGEs and cause of neurodegeneration in AD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation